Cisplatin and Short-Term 5-Fluorouracil Infusion for Paraneoplastic Microangiopathic Hemolytic Anemia in Gastric Cancer: A Case Report and Review of the Literature. (29th December 2013) - Sanatani, M. S.; Lazo-Langner, A.; Al-Rasheedy, I. M.
Abstract : Microangiopathic hemolytic anemia is a rare paraneoplastic syndrome accompanying adenocarcinoma of the stomach. We report on a patient presenting with anemia due to a combination of severe hemolysis and tumour bleeding, where the combination of cisplatin and 5-fluorouracil in a short course infusional regimen led to a complete response of the hematologic abnormalities in the first line setting. Relapse was successfully treated with second line docetaxel; however the response was relatively short-lived. Overall survival was 16 months from diagnosis, which compares favourably to the survival of other reported cases. The chemotherapy regimens used in previously reported similar cases are reviewed. We suggest that a regimen based on bolus 5-fluorouracil, possibly with a platinum, should be investigated as a possible regimen of choice.